The effects of beetroot juice supplementation on performance of male soccer players - Abniki, I.; Mohebbi, H.; Ebrahimi, M. (Science, Movement & Health, 2026)
Aim. The current study aimed to investigate the effects of consuming nitrate-rich beetroot juice (BJ), both in acute and short-term scenarios, on aerobic/anaerobic performance and subsequent alteration of heart rate (HR) and blood pressure (BP) of young male soccer players. Methods. This randomized crossover study was conducted with 12 male soccer players who met the research criteria. In the acute phase of the study, half of the subjects randomly consumed natural BJ (80 mL, containing 6.5 mmol of nitrate), while the other half consumed a placebo (80 ml of colored/flavored water) and, 120 minutes later, performed the Wingate and Shuttle Run tests. After 72 hours, the tests were repeated with other supplements. For the short-term part, half of the subjects randomly underwent a 6-day protocol of consuming BJ or placebo in a crossover manner with an interval of one-week wash-out period. 24 hours after the last meal, the tests were repeated. HR and BP were monitored through the trials. Repeated measure analysis of variance and Bonferroni tests were used for data analysis in IBM SPSS software version 26 (P < 0.05). Results. SBP and HR were reduced 2 hours after BJ intake. The effect of acute and short-term consumption of beetroot juice on anaerobic power was insignificant, while the fatigue index and time at peak power improved with acute BJ intake. Aerobic performance improved both in acute and short-term phases. Conclusions. male soccer players may get benefits from the acute intake of BJ before events.